(untitled) (Diversity Research: Journal of Analysis and Trends, 2023)
The article presents the results of an empirical study of socio-psychological determinants of achievement motivation in educational activities. Relationships between achievement motivation and indicators of socio-psychological properties of a person with a high/low level of achievement motivation were revealed. It is shown that as sociopsychological determinants of motivation to achieve success in educational activities are a fairly high level of formation of standards of behavior, business orientation, the ability to selfregulate, intellectual activity, the ability to mobilize; dissatisfaction with one’s results strengthens achievement motivation